Psychological Aspects of the Main Character in A Man Called Otto Movie (2022) - Nyoman Putri Tarani Gayatri; I Nyoman Aryawibawa; Ni Ketut Alit Ida Setianingsih (Pusat riset dan Inovasi Nasional, 2025)
This research aims to analyze the psychological aspects of the main character, Otto Anderson, in the movie A Man Called Otto (2022), using Bernhardt’s (1953) theory of psychology. The study identifies five key aspects of human motivation reflected in Otto’s character: appetites, wants, emotions, feelings and attitudes, and social motives. This research uses a qualitative method and applies descriptive analysis to examine the character's psychological behavior. Data were collected using the documentation method by selecting specific scenes from the film and classifying them based on Bernhardt’s categories. The analysis reveals that Otto’s behavior is deeply influenced by his psychological state, especially in response to the loss of his wife. Each psychological aspect demonstrates how his internal motivations are shaped by grief and gradually shift toward emotional healing and renewed engagement with others. This study contributes to the understanding of character development through psychological analysis in film narratives.